Emerging Alzheimer's disease treatment paradigms: A late-stage clinical trial review - Hlávka, Jakub P; Kinoshita, Andrew T; Jeyasingh, Divya; Huang, Cheng; Mirsafian, Leila; Jacobson, Mireille (Alzheimer's & dementia, 2024)
INTRODUCTION: Without disease-modifying interventions, Medicare and Medicaid spending on Alzheimer's disease (AD) management is expected to reach 637 billion USD annually by 2050. The recent advent of promising AD therapies after decades of a near-total failure rate in clinical trials suggests that more disease-modifying therapies are on the horizon. In this review, we assess the late-stage pipeline of disease-modifying candidates for AD and offer a novel classification of intervention candidates by treatment paradigms-groups of candidates that share an underlying biological mechanism of action and general disease target. METHODS: We extracted data from the National Library of Medicine clinical trials database regarding Phase 2 and 3 trials of disease-modifying AD therapies. We categorized trials into eight unique treatment paradigms, which we defined by combinations of therapy (biologic, small molecule, cell and gene therapy, other) and target (amyloid, tau, other). We analyzed primary endpoints, eligibility criteria including clinical ratings of cognition, trial phase and length, and funding sources. RESULTS: We identified 123 unique disease-modifying intervention candidates in 175 late-stage clinical trials. Biologic and small molecule drugs comprised 30% and 54% of trials, respectively. Eligibility criteria favored patients between the ages of 60 and 80 years with mild cognitive impairment. Including multi-phase trials, 81% of studies were engaged in Phase 2 and 27% in Phase 3. Notably, within the Biologic-Amyloid paradigm, 64% of trials were engaged in Phase 3. DISCUSSION: Current studies of disease-modifying therapies for AD comprise a diverse set of approaches to treating the disease. However, effort is largely concentrated in a few treatment paradigms and a narrow patient population, causing varying rates of progress among treatment paradigms in the late-stage clinical trial pipeline. Strategies may be warranted to accelerate successes in the most promising therapeutical paradigms and nurture growth within nascent areas lacking resources but not potential. HIGHLIGHTS: An analysis of Alzheimer's disease trial treatment paradigms was conducted.From April 2021 to March 2023, 175 trials of 123 unique candidates were reviewed.Biologic and small molecule drugs comprised 30% and 54% of trials, respectively.Eligibility criteria favored ages 60 through 80 with mild cognitive impairment.